The molecular mechanism association between periodontitis and chronic obstructive pulmonary disease - ZHANG Xinyun, MAO Guangtong, WANG Jintao, HE Rui, ZHONG Liangjun, LIU Kai (Kouqiang yixue)
Chronic obstructive pulmonary disease is a pulmonary disease characterized by persistent, progressive airflow restriction and chronic inflammation, which is closely related to the occurrence and development of periodontitis. There are common risk factors and mutual influence between the two diseases. Based on existing studies, this paper discusses the correlation between periodontitis and chronic obstructive pulmonary disease and its influence on patients from the perspective of common molecular mechanisms, in order to provide theoretical guidance for optimizing clinical treatment.